2021
DOI: 10.5588/ijtld.21.0345
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects and duration of treatment of TB in Canterbury, New Zealand

Abstract: BACKGROUND Treatment of TB is often extended beyond the recommended duration. The aim of this study was to assess prevalence of extended treatment and to identify associated risk factors. We also aimed to determine the frequency and type of adverse drug reactions (ADR) experienced by this study population.METHODS We performed a retrospective cohort study of all patients treated for active TB at Christchurch Hospital, Christchurch, New Zealand, between 1 March 2012 and 31 December 2018. Data for 192 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The present study revealed that the prevalence of ADRs was 29% among the study population, similar to various worldwide studies ranging from 8% to 85%. [3][4][5][6]14,[17][18][19][20] Several studies reported more ADR prevalence in drug-resistant TB patients, similar to the present study, where 50% of DRTB patients experienced ADRs. 19,[21][22][23] The variance in ADR prevalence between these studies could be due to several data collection variables including the ADR reporting mechanism, patient-reported (subjective) or clinician-detected (objective), and variations in the use of particular anti-tubercular drugs such as dosage and ancillary medications used for ADR management.…”
Section: Discussionsupporting
confidence: 87%
“…The present study revealed that the prevalence of ADRs was 29% among the study population, similar to various worldwide studies ranging from 8% to 85%. [3][4][5][6]14,[17][18][19][20] Several studies reported more ADR prevalence in drug-resistant TB patients, similar to the present study, where 50% of DRTB patients experienced ADRs. 19,[21][22][23] The variance in ADR prevalence between these studies could be due to several data collection variables including the ADR reporting mechanism, patient-reported (subjective) or clinician-detected (objective), and variations in the use of particular anti-tubercular drugs such as dosage and ancillary medications used for ADR management.…”
Section: Discussionsupporting
confidence: 87%
“…Depending on the type of medication, it may be taken regularly (e.g., for chronic diseases), or intermittently (e.g., for symptom relief). There was a relatively low rate of TB-ADR (11%) compared to rates in the literature 39,40 and this may have affected the performance of the prediction model. Moreover, the lack of association between CM and risk of TB-ADR among PWH may have been due to the sample size; and because we only considered baseline information about ART, and not the possible time-varying association of ART and TB-ADR.…”
Section: Discussionmentioning
confidence: 84%